Queer Reflections on AI: Uncertain Intelligences - Michael Klipphahn-Karge; Ann-Kathrin Koster; Sara Morais dos Santos Bruss (Routledge, 2024)
This volume offers a socio-technical exploration of Artificial Intelligence (AI) and the way it reflects and reproduces certain normative representations of gender and sexuality, to ultimately guide more diverse and radical discussions of life with digital technologies. Moving beyond the examination of empirical examples and technical solutions, the book approaches the relationship between queerness and AI from a theoretical perspective that posits queer theory as central to understanding AI differently. The chapters pose questions about the politics and ethics of machine embodiments and data imaginaries on the one hand, and about technical possibilities for a production of social identities characterised by shifting diversity and multiplicity on the other, as they are mediated by and through digital technologies. Transgressing disciplinary boundaries to engage a diversity of conceptual tools, critical approaches, and theoretical traditions, this book will be an important resource for students and researchers of gender and sexuality, new media and digital cultures, cultural theory, art and visual culture, and AI.
Keywords: 300